TAFSIR SAINTIFIK AYAT HEWAN DALAM AL-QUR’AN: ANALISIS LALAT DALAM QS. AL-HAJJ: 73 DAN RAYAP DALAM QS. SABA’: 14 - Ahmad Al-Amin; Muhammad Semman; Akhmad Dasuki (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Qur’an uses various animal metaphors to convey theological and scientific messages, including the fly in Surah Al-Hajj: 73 and the termite in Surah Saba’: 14. This study aims to analyze these two verses using the Scientific Exegesis approach to uncover the scientific implications behind the mention of these two insects. The results of the study indicate that the Qur’an’s challenge regarding the inability to reclaim something seized by a fly is closely linked to the fly’s extracellular digestion process, which chemically transforms substances in a short period of time. Meanwhile, the role of termites in revealing the death of Prophet Solomon (peace be upon him) demonstrates a systematic mechanism of cellulose degradation, which proves the limitations of the jinn’s knowledge regarding the unseen. This integration between the sacred text and modern biological discoveries reinforces the argument that every detail in the Qur’an has an accurate empirical basis..